Retinal nerve fiber layer reflectance for early glaucoma diagnosis - Liu, Shuang (2014)
PURPOSE: Compare performance of normalized reflectance index (NRI) and retinal nerve fiber layer thickness (RNFLT) parameters determined from OCT images for glaucoma and glaucoma suspect diagnosis. METHODS: Seventy-five eyes from seventy-one human subjects were studied: 33 controls, 24 glaucomatous, and 18 glaucoma-suspects. RNFLT and NRI maps were measured using two custom-built OCT systems and the commercial instrument RTVue. Using area under the receiver operating characteristic (ROC) curve, RNFLT and NRI measured in seven RNFL locations were analyzed to distinguish between control, glaucomatous, and glaucoma-suspect eyes. RESULTS: The mean NRI of the control group was significantly larger than the means of glaucomatous and glaucoma-suspect groups in most RNFL locations for all three OCT systems (p<0.05 for all comparisons). NRI performs significantly better than RNFLT at distinguishing between glaucoma-suspect and control eyes using RTVue OCT (p=0.008). The performances of NRI and RNFLT for classifying glaucoma-suspect vs. control eyes were statistically indistinguishable for PS-OCT-EIA (p=0.101) and PS-OCT-DEC (p=0.227). The performances of NRI and RNFLT for classifying glaucomatous vs. control eyes were statistically indistinguishable (PS-OCT-EIA: p=0.379; PS-OCT-DEC: p=0.338; RTVue OCT: p=0.877). CONCLUSIONS: NRI is a promising measure for distinguishing between glaucoma-suspect and control eyes and may indicate disease in the pre-perimetric stage. Results of this pilot clinical study warrant a larger study to confirm the diagnostic power of NRI for diagnosing pre-perimetric glaucoma.